2021
DOI: 10.3390/f12121709
|View full text |Cite
|
Sign up to set email alerts
|

Properties of Plywood Made from Perforated Veneers

Abstract: The paper is focused on the bending properties of beech plywood made from veneers with perforations. The modification of the plywood was done by the targeted perforations in veneers used. The perforations were rectangular in shape 5 × 30 mm. There was a gap of 10 mm between the perforations (in each direction) and the perforations in the individual rows were shifted by 10 mm relative to each other. Two structures of lightweight plywood were investigated: sheathed (lightweight type 1) with perforated inner laye… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 20 publications
0
2
0
Order By: Relevance
“…Based on the results obtained for the physical and mechanical properties of all tested hybrid panels, it can be concluded that peeler cores can be utilised as a raw material for producing hybrid plywood. The density-to-strength ratios of this lightweight plywood were also very promising [25]. Applying peeler cores as a filler in the core layer of hybrid lightweight plywood is rational and allows maximum utilisation.…”
Section: (D)mentioning
confidence: 97%
“…Based on the results obtained for the physical and mechanical properties of all tested hybrid panels, it can be concluded that peeler cores can be utilised as a raw material for producing hybrid plywood. The density-to-strength ratios of this lightweight plywood were also very promising [25]. Applying peeler cores as a filler in the core layer of hybrid lightweight plywood is rational and allows maximum utilisation.…”
Section: (D)mentioning
confidence: 97%
“…Murara et al (2005) evaluated two sawmilling systems and found that yield is affected by the sawmilling system according to the diameter of the log; in the traditional system they found no increase in yield with increasing diameter, but yield improved with an optimized system as the diameter of the logs increased. Meanwhile, Vaughan et al (2018) and Fekiač et al (2021) indicate that the continuous deterioration of raw material in the field can affect the potential yield and quality of forest products; also, Monserud et al (2004) mention that twisted or curved logs have potentially lower yields.…”
Section: Rendimiento Por Largo Nominalmentioning
confidence: 99%
“…Priority should be given to the plywood industry due to the high quality of the raw material, followed by the sawmill industry for thick and thin diameters. Kallakas et al (2020) and Fekiač et al (2021) mention that the main industry to be supplied at the end of the shift from intensively managed forests is plywood, due to the high quality of the logs and a low percentage of knots. Finally, the secondary products of the sawmill and the production of particle boards based on sawdust and chips will benefit from the primary transformation.…”
Section: Origin Of Solid Waste Processingmentioning
confidence: 99%
“…At the individual tree level (considering mature trees from 25 to 30 meters high), it is possible to obtain product for various industrial uses. Mainly, the production of plywood is obtained from the base of the tree (4.88 meters length), because it is where the largest diameter of the log and the highest quality free of defects occur (Fekiač et al, 2021). High-and medium-quality lumber is derived from the second and third section of the log (9.75 meters length, as larger diameter logs tend to produce a higher volume of quality lumber (Borz et al, 2021;Orozco et al, 2017).…”
Section: Origin Of Solid Waste Processingmentioning
confidence: 99%